Observing the energetic universe at very high energies with the VERITAS gamma ray observatory. Issue 10 (15th November 2018) - Mukherjee, R.; ,
Abstract: Very high energy gamma-ray observations offer indirect methods for studying the highest energy cosmic rays in our Universe. The origin of cosmic rays at energies greater than 10 18 eV remains a mystery, and many questions in particle astrophysics exist. The VERITAS observatory in southern Arizona, USA, carries out an extensive observation program of the gamma-ray sky at energies above 85 GeV. Observations of Galactic and extragalactic sources in the TeV band provide clues to the highly energetic processes occurring in these objects, and could provide indirect evidence for the origin of cosmic rays and the sites of particle acceleration in the Universe. VERITAS has now been operational for ten years with the complete array of four atmospheric Cherenkov telescopes. In this review, we present the status of VERITAS, and give few results from three of its key scientific programs: extragalactic science, Galactic physics, and study of fundamental physics and cosmology.